A Text-Mining-Based Approach for Conducting Literature Review of Selected Meshfree Methods - Sindhusuta, S.; Chi, Sheng-Wei; Derrible, Sybil (Computer Assisted Methods in Engineering and Science, 2022)
The goal of this study is to review the literature in the field of meshfree methods using text mining. For this study, the abstracts of around 17 330 relevant articles published from 1990 to 2020 were collected from Scopus. Text mining techniques such as the latent Dirichlet allocation (LDA), along with the calculation of term frequencies and co-occurrence coefficients were used to analyze the text. The study identified a few key topics in the field of meshfree methods and helped to see the evolution of the field over the past three decades. Furthermore, the trend in the number of publications and frequency map highlighted research trends and lack of focus in certain areas. The co-author network visualization provided interesting insights about collaboration between different researchers around the world. Overall, this study facilitates a systematic literature review in the field of meshfree methods and provides a broader perspective of the field to the research community.